Reflection on Teaching Practice as a Strategy for Innovation in Legal Training - Elgueta Rosas, María Francisca (2021)
Reflective praxis is a relevant instrument for permanent innovation in the training process. Strengthening the ability to ask questions and solve pedagogical problems, using research as a tool for reflecting on one’s ownwork, would be a contribution to the comprehensive approach to changes in the teaching practices of law professors. We propose, therefore, to highlight the value of the creation of a research culture of the teaching profession itself and to present a strategy, in broad strokes, for the implementation of a reflective praxis. Teaching practice in legal training is structured in a pedagogical, disciplinary, evaluative and curricular framework in relation to the context in which it occurs and the beliefs and visions of the teacher who executes it. In addition, it is the product of the conception that teachers have about what law is and can be formalistic, critical-realistic or argumentative-democratic.